Implementasi Server Dengan Sistem Operasi Linux Debian Sebagai Pendukung Penerimaan Peserta Didik Baru Dengan Virtualbox Di SMK Bina Islam Mandiri Kersana Kabupaten Brebes - Adhi Santoso, Nugroho; Nugroho, Bangkit Indarmawan; Surorejo, Sarif; Santoso, Bayu Aji; Murtopo, Aang Alim; Syefudin, Syefudin; Arif, Zaenul; Kurniawan, Rifki Dwi; Karsidin, Karsidin (Fakultas Komputer Dan Desain, 2025)
Every job that is done using computer network technology, the data that we input has actually entered the server computer. Thus the data that we have entered will be automatically saved to the server computer. The real conditions in the field are that there are several things that may cause the PPDB process at SMK Bina Islam Mandiri Kersana, Brebes Regency to be less effective. The main causes are Human Resources, Hardware, PPDB Process and Software. The design of the computer network that will be used as the object of this study, one of the topologies used is the star topology. The materials for designing the implementation of this server are the server computer, client computer, switch and PPDB application. To be able to connect to a network, here it is necessary to have a server IP address which will later be used to connect to other computers in this case the client computer. Previously, install Linux Debian using the VirtualBox application for the server, then configure the network until finished, connect the server computer to the client computer using the media, namely the UTP cable, after that on the client computer set the IP and open the browser to see the results. So it can be concluded that the server system for accepting new students can be done easily, as long as there is a will and perseverance in making it.